Analisis Implementasi Kebijakan Publik dalam Meningkatkan Kualitas Pelayanan Publik di Indonesia - Halawa, Netral Wulan Kartika; Hia, Mesrawati; Gulo, Alvian Putri; Ndraha, Andayanti; Marulafau, Harni Sartika; Zega, Juli Lestarina; Waruwu, Imelda Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of public policies in improving the quality of public services in Indonesia. The research focuses on how policy implementation is carried out by government institutions, the supporting and inhibiting factors, and its impact on service effectiveness. The methodology includes a literature review and analysis of various policies, regulations, and empirical findings related to public service delivery. The results reveal that the success of policy implementation is influenced by bureaucratic commitment, inter-agency coordination, human resource capacity, and the availability of adequate facilities and infrastructure. However, challenges such as overlapping regulations, complex bureaucratic procedures, and weak supervision often hinder efforts to enhance public service quality. This study emphasizes that optimizing policy implementation requires improved transparency, accountability, and stronger collaboration between the government and society.